A Study of the Relationship Between Teachers’ Perceptions of Their Leadership Capacity and Organizational Culture at the Basic Education High Schools in Thanbyuzayat Township, Mon State, Myanmar - Latt, Zaw Tun; Ye, Yan (Scholar: Human Sciences, 2021)
The aim of this study was to determine the relationship between teachers’ perceptions of their leadership capacity and organizational culture at the Basic Education High Schools in Thanbyuzayat Township, Mon State, Myanmar. The participants were 113 full-time teachers from Basic Education High Schools (No.1&2) during the academic year of 2019-2020. The researcher adopted the survey-High Leadership Capacity School Survey by Lambert (2003) and the survey-Organizational Culture (OCS) by Saravanan (2013). The collected data from each survey was analyzed by Descriptive Statistics, Frequency and Percentage, Mean and Standard Deviation, and Pearson Product Moment Correlation Coefficient. The study results indicated that the level of teachers’ perceptions of their leadership capacity was Moderate, and organizational culture was Positive. Consequently, it was determined that the relationship between the two variables was found to be Significant, however it was interpreted that the relationship between the two was weak due to the correlation (r) value of .388**. The findings suggested that teachers needed to create more opportunities and time for personal reflection for they would help them grow in their profession. In addition, to build collaborative and participative culture which could increase a healthy workplace was also recommended and the school organizations should also upgrade the quality of materials provided to teachers in teaching and learning process as well as innovative technologies should also be realized in order to keep abreast with the 21st century education.